Polarized protons acceleration at U-70 - Otboyev, A.V.; Shatunov, P.Yu.; Shatunov, Yu.M. (Вопросы атомной науки и техники, 2006)
A possibility to accelerate polarized proton at the synchrotron U-70 is considered. Estimations of the spin resonances
are given in the energy range 2.5…70 GeV. To suppress depolarizing effects of spin resonances, a scheme of
three partial Siberian snakes is suggested. Each snake consists from helical magnets with 4.5 T magnetic field. The
scheme provides the adiabatic spin flip at imperfection resonances and suppresses all intrinsic resonances by quite
realistic beam emittance and magnets misalignments ±5 mm. В статье обсуждается возможность ускорения поляризованных протонов в синхротроне У-70. Дана оценка силы деполяризующих резонансов. Предлагается схема из трех спиральных частичных Сибирских змеек для подавления деполяризующего влияния, как целых, так и спибетатронных резонансов. Обсуждается конструкция спиральных магнитов и требования к качеству пучка и магнитной системы синхротрона У-70. У статті обговорюється можливість прискорення поляризованих протонів у синхротроні У-70. Дана
оцінка сили деполяризуючих резонансів. Пропонується схема із трьох спіральних часткових Сибірських
змійок для придушення деполяризуючого впливу, як цілих, так і спин-бетатронних резонансів.
Обговорюється конструкція спіральних магнітів і вимоги до якості пучка і магнітної системи синхротрона
У-70.